Implementasi Kurikulum Ektra Kurikuler Berbasis Program Pendidikan Damai Pada Sma Di Kabupaten Aceh Besar - Sayuti Malik (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
Peace education program implemented at formal schools may positively affect students’ behavior. The objective of this research was to identify planning, implementation, and evaluation system of peace education program at senior high schools in Aceh Besar Regency. This research was conducted by means of descriptive method with qualitative approach. Observation, interview, and documentation were the techniques used in data collection. The subjects of this research were the principals, the teachers who teach for peace education program, and the facilitators of the program. The results showed that the teachers at three senior high schools where the research took place were well-prepared and tried to master the materials before teaching. In addition, the teaching methods used were based on the curriculum. Moreover, written and spoken evaluation to the program was done by observing the behavior of the students. The materials taught were also based on the syllabus. The syllabus has been trained by the Instituion of Peace Education Program for Aceh and has been compiled in a textbook for second grade students of senior high schools entitled “Kurikulum Aqidah Akhlak dalam Konteks Pendidikan Damai” (the Curriculum of Faith-Moral in the Context of Peace Education).